Investigation of Cold Rolling Influence on near Surface Residual Stress Distribution in Explosive Welded Multilayer - Sedighi, M.; Honarpisheh, M. (Проблемы прочности, 2012)
The aim of this study is to investigate the effect of cold rolling on residual stress distribution of aluminum and copper three-ply clad sheets fabricated by explosive welding. After preparation of the explosive-welded multilayer, explosivewelded Al/Cu/Al specimens were rolled at 11, 30, 40, and 56% thickness reduction. The through-depth residual stress profiles near the surface have been extracted for explosivewelded and cold-rolled multilayers by incremental hole-drilling method. Results show that the surface of explosive-welded multilayer is subjected to high tensile residual stresses and will be reduced by cold rolling process. Also, tensile residual stress at the surface of cold-rolled multilayers increases at higher thickness reduction.